Factors that contribute to fraud under SOCSO insurance scheme / Nor Faizah Hassan - Hassan, Nor Faizah (Faculty of Business and Management, 2010)
The purpose of this research is to study the factors that contribute to fraud under SOCSO Insurance Scheme. This research carried out regarding many frauds occurred in SOCSO. Therefore the research is done to identify several factors that contribute to fraud in SOCSO. The factors such as financial problem, ineffective internal control and attitude are studied. SOCSO is developed to give protection for employees against industrial accident including occupational disease and accidents while traveling for work related purpose. Beside that there is other benefit that provided by SOCSO like Invalidity Pension Scheme include coverage to employees against invalidity or death due to any cause, medical treatment, physical and vocational rehabilitation services. However, many problems occur regarding to the availability of many coverage and they start to take advantage. The survey is conducted at SOCSO RAWANG office. The sample size for this study is 30 customers. There were 30 questionnaires distributed to the customers of SOCSO RAWANG and all 30 questionnaires were returned. The data obtained using two methods that are primary and secondary data. Data analyzed using Reliability Test, Frequency Distribution, Regression and Mean data through SPSS Program.